A cultural history of Japanese Buddhism - Deal, William E.; Ruppert, Brian Douglas, 1962- (Chichester, West Sussex, Uk ; Malden, MA USA : Wiley, Blackwell, 2015)
"Offers a vivid, nuanced, and chronological account of Buddhistreligion in Japan -- from its emergence in the sixth centuryright through to the present day"--
Includes bibliographical references and index.
Keywords: Buddhism -- Japan -- History; Buddhism and culture -- Japan -- History; RELIGION / Buddhism / General (see also PHILOSOPHY / Buddhist).